Monitoring the chemical changes in fingermark residue over time using synchrotron infrared spectroscopy - Boseley, Rhiannon; Vongsvivut, J.; Appadoo, D.; Hackett, Mark; Lewis, Simon (The Royal Society of Chemistry, 2022)
Degradation of fingermark residue has a major impact on the successful forensic detection of latent fingermarks. The time course of degradation has been previously explored with bulk chemical analyses, but little is known about chemical alterations within specific regions of the fingermark, which is difficult to study with bulk measurement. Here we report the use of synchrotron-sourced attenuated total reflection-Fourier transform infrared (ATR-FTIR) microspectroscopy to provide spatio-temporal resolution of chemical changes within fingermark droplets, as a function of time since deposition, under ambient temperature conditions. Eccrine and sebaceous material within natural fingermark droplets were imaged on the micron scales at hourly intervals from the time of deposition until the first 7–13 hours after deposition, revealing that substantial dehydration occurred within the first 8 hours. Changes to lipid material were more varied, with samples exhibiting an increase or decrease in lipid concentration due to the degradation and redistribution of this material. Across 12 donors, it was noticeable that the initial chemical composition and morphology of the droplet varied greatly, which appeared to influence the rate of change of the droplet over time. Further, this study attempted to quantify the total water content within fingermark samples. The wide-spread nature and strength of the absorption of Terahertz/Far-infrared (THz/Far-IR) radiation by water vapour molecules were exploited for this purpose, using THz/Far-IR gas-phase spectroscopy. Upon heating, water confined in natural fingermarks was evaporated and expanded in a vacuum chamber equipped with multipass optics. The amount of water vapour was then quantified by high-spectral resolution analysis, and fingermarks were observed to lose approximately 14–20 μg of water. The combination of both ATR-FTIR and Far-IR gas-phase techniques highlight important implications for experimental design in fingermark research, and operational practices used by law enforcement agencies.